Long‐Term angiographic follow‐up after successful repeat balloon angioplasty for in‐stent restenosis - Foti, Rosario (Clin Cardiol, 2009)
Background: Coronary stent implantation is associated with improved angiographic short‐term and mid‐term clinical outcome. However, restenosis rate still remains between 20 and 30%. Hypothesis: The purpose of the study, performed as a prospective angiographic follow‐up to detect restenosis, was to evaluate the immediate and the 6‐month angiographic results of repeat balloon angioplasty for in‐stent restenosis. Methods: From April 1996 to September 1997, 335 stenting procedures performed in 327 patients underwent prospectively 6‐month control angiography. Of the 96 lesions that showed in‐stent restenosis (>50% diameter stenosis) (29%), 72 underwent balloon angioplasty. Results: The primary success rate was 100%. Follow‐up angiogram at a mean of 6.9 ± 2.4 months was obtained in 54 patients. Recurrent restenosis was observed in 24 of the 55 stents (44%). Repeat intervention for diffuse and body location in‐stent restenosis before repeat intervention was associated with significantly higher rates of recurrent restenosis (p < 0.001 and p < 0.05, respectively). Of the 19 patients who underwent further balloon angioplasty (100% success rate), coronary angiography was performed in 18 (95%) at a mean of 8.2 ± 2.0 months and showed recurrent restenosis in 12 patients (67%). Further repeat intervention for diffuse and severe in‐stent restenosis before the second repeat intervention was associated with significantly higher rates of further recurrent restenosis (p < 0.05 and p < 0.005, respectively). Conclusions: Although balloon angioplasty can be safely, successfully, and repeatedly performed after stent restenosis, it carries a progressively high recurrence of angiographic‐restenosis rate during repeat 6‐month follow‐ups. The subgroup of patients with diffuse, severe, and/or body location in‐stent restenosis proved to be at higher risk of recurrent restenosis.